Looking at human healthcare to improve agricultural service delivery: The case of online chatgroups - Sarunas Jomantas; Anna Wood; Nyamwaya Munthali; Willis Ochilo; Manju Thakur; Dannie Romney; Mariam Kadzamira (CABI, 2024)
Abstract This study analyses the opportunities and pitfalls of using chatgroups for plant health systems. It also examines the conditions for strengthening chatroom functions and considers the possibility of replicating reported successes in healthcare settings to plant health systems. We use mixed qualitative methods, which include stakeholder surveys and observation of chatgroup activity interactions in Ghana, Kenya, Uganda and Sri Lanka. Our findings show that there is evidence of the benefits of chatgroups to human health which can be replicated in plant health. Replication should, however, not be a 'copy and paste' approach. This is due to the general lack of evidence-based guidelines and lessons learned to move beyond the initial adoption success of communication applications. Also, in practice, plant doctor chatgroups are generally much larger than groups in healthcare settings and it remains to be seen whether increasing chatroom activity could benefit specific plant health objectives; or whether it would lead to increased labour costs, and/or diminish the participation of plant doctors. One Health impact statement The article is relevant in a One Health context as it demonstrates that there is a lot to learn between sectors about interventions and approaches. The work used literature from human health interventions to shed light on how a similar intervention in plant health functioned and could be improved. It shows that if actors in the plant health sector had engaged early on with actors in the human health sector, they may have avoided pitfalls in the ways that chatgroups can be used to support plant health management. It is expected that human, animal and plant health sectors would benefit from the knowledge and recommendations in this article to establish new online chatgroups that can support transformative change.